STATICS BEHAVIOR OF INTERFERENCE FIT OF CRH2 EMUS’ BEARING-AXLE COUPLING SYSTEM - CAO QingSong; XIANG Qin; XIONG GuoLiang; ZHU ZhiQiang (Jixie qiangdu)
To the interference fit surface of EMUs’ bearing-axle coupling system occurred fretting damage frequently,the solid model and finite element model of the CRH2 EMUs’ bearings-axle coupling system were established with considering the influence of load and interference. The statics behavior of bearing-axle system was studied by analyzing the stress distribution and deformation of matching surface under different routes or multiple interference. The results show that the maximum stress of the curving route is larger than the straight route under the same interference. The maximum stress and plastic deformation would become larger with the increasing of interference on the same route. While the interference was 0. 15 mm which exceeded the maximum allowable range,bearing inner race arose crack. The research can provide reference for the study on fretting problem of interference fit of EMUs’ bearings-axles system.